Comprehensive phenotypic and functional analysis of dominant and recessive FOXE3 alleles in ocular developmental disorders. Issue 17 (27th May 2021) - Reis, Linda M; Sorokina, Elena A; Dudakova, Lubica; Moravikova, Jana; Skalicka, Pavlina; Malinka, Frantisek; Seese, Sarah E; Thompson, Samuel; Bardakjian, Tanya; Capasso, Jenina; Allen, William; Glaser, Tom; et al.
Abstract: The forkhead transcription factor FOXE3 is critical for vertebrate eye development. Recessive and dominant variants cause human ocular disease but the full range of phenotypes and mechanisms of action for the two classes of variants are unknown. We identified FOXE3 variants in individuals with congenital eye malformations and carried out in vitro functional analysis on selected alleles. Sixteen new recessive and dominant families, including six novel variants, were identified. Analysis of new and previously reported genetic and clinical data demonstrated a broad phenotypic range with an overlap between recessive and dominant disease. Most families with recessive alleles, composed of truncating and forkhead-domain missense variants, had severe corneal opacity (90%; sclerocornea in 47%), aphakia (83%) and microphthalmia (80%), but some had milder features including isolated cataract. The phenotype was most variable for recessive missense variants, suggesting that the functional consequences may be highly dependent on the type of amino acid substitution and its position. When assessed, aniridia or iris hypoplasia were noted in 89% and optic nerve anomalies in 60% of recessive cases, indicating that these defects are also common and may be underrecognized. In dominant pedigrees, caused by extension variants, normal eye size (96%), cataracts (99%) and variable anterior segment anomalies were seen in most, but some individuals had microphthalmia, aphakia or sclerocornea, more typical of recessive disease. Functional studies identified variable effects on the protein stability, DNA binding, nuclear localization and transcriptional activity for recessive FOXE3 variants, whereas dominant alleles showed severe impairment in all areas and dominant-negative characteristics.